Investigación de tecnología sostenible para la vivienda VIS ubicado en la localidad de Bosa de la ciudad de Bogotá - Martínez Salgado, David (Universidad Antonio Nariño, 2022)
This research project exposes the different sustainability problems presented by the type of VIS housing in the town of Bosa in the city of Bogotá. Due to this, a data collection is carried out in official and governmental information sources and strategic documentation, which demonstrate the most relevant variables and the conditions that affect housing, for example, the high energy consumption in the city of Bogotá, which they are generated mainly by the high concentration of residential use in some localities such as Bosa, Suba and Kennedy between 2008 and 2012 the capital increased energy consumption by 4%, going from 3,500 Gwh to 3,700 Gwh respectively (Martínez, 2013 ) and, in addition to the high population density and the growth of VIS housing projected in recent years.